Does Pedestrian Danger Mediate the Relationship between Local Walkability and Active Travel to Work? - Slater, Sandy J.; Nicholson, Lisa; Abu Zayd, Haytham; Chriqui, Jamie Friedman (Frontiers in Public Health, 2016)
Background: Environmental and policy factors play an important role in influencing people’s lifestyles, physical activity (PA), and risks for developing obesity. Research suggests that more walkable communities are needed to sustain lifelong PA behavior, but there is a need to determine what local built environment features facilitate making being active the easy choice. Purpose: This county-level study examined the association between local walkability (walkability and traffic calming scales), pedestrian danger, and the percent of adults who used active transport to work. Methods: Built environment and PA outcome measures were constructed for the 496 most populous counties representing 74 percent of the U.S. population. GIS-based walkability scales were constructed and include a census of roads located within the counties using 2011 Navteq data. The pedestrian danger index (PDI) includes data collected from the Fatality Analysis Reporting System 2009-2011, and measures the likelihood of a pedestrian being hit and killed by a vehicle. Four continuous outcome measures were constructed using 2009-2013 American Community Survey county-level 5-year estimates. The measures represent the percentage of workers living in a county who worked away from home and: 1) walked to work; 2) biked to work; 3) took public transit; and 4) used any form of active transport. Linear regression and mediation analyses were conducted to examine the association between walkability, PDI and active transport. Models accounted for clustering within state with robust standard errors, and controlled for median household income, families with children in poverty, race, ethnicity, urbanicity and region. Results: The walkability scale was significantly negatively associated with the PDI (β=-0.06, 95% CI=-0.111, -0.002). In all models, the PDI was significantly negatively associated with all active travel-related outcomes at the p<0.01 level. The walkability scale was positively associated with all four outcomes at the p<0.01 level. Results showed that the significant positive relationship between local walkability and the four active transport outcome measures was partially mediated by the PDI. We found no association between traffic calming, the PDI, and the active transport outcomes. Conclusion: County-level walkability is associated with active travel, and this association is partially mediated by an index of pedestrian safety.